Exhaust gas purification catalyst
By designing a multi-layer catalyst structure in the exhaust purification catalyst, using the combination of Rh and Pd and the distribution and particle size control of the catalyst metal particles, the problems of insufficient low-temperature purification activity and insufficient OSC function are solved, and more efficient exhaust purification is achieved.
Patent Information
- Application Number
- CN202411119751.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-08-15
- Publication Date
- 2025-03-11
AI Technical Summary
The existing catalysts for exhaust purification are insufficient in low temperature purification activity at low temperatures, and the OSC function is insufficient at high temperatures, resulting in a degradation of purification performance.
A multi-layer catalyst structure with a substrate and arranged on the substrate is adopted, wherein the lower catalyst layer contains Rh, the upper catalyst layer consists of two layers on the upstream and downstream sides, and at least the upstream side layer contains Pd, and the distribution and particle size of the catalyst metal particles are controlled to improve the contact frequency and oxygen storage capacity.
Improves the low-temperature purification activity and fully ensures the OSC function at high temperatures, thereby improving the exhaust purification performance.
Smart Images

Figure CN119588432A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an exhaust gas purifying catalyst comprising a substrate and a catalyst layer provided on the substrate. Background Art
[0002] The exhaust gas discharged from the internal combustion engine of automobiles and the like contains harmful components such as HC (hydrocarbons), CO (carbon monoxide), and NOx (nitrogen oxides). In order to remove these harmful components from the exhaust gas, an exhaust gas purification catalyst having a substrate and a catalyst layer arranged on the substrate is used, and the catalyst layer includes a powder material containing a powdered carrier, an OSC material (oxygen storage material), etc., and catalyst metal particles supported on the carrier. Catalyst metals, for example, use Pt (platinum), Pd (palladium), Rh (rhodium), etc. Among the catalyst metals, Pd, which has high purification performance for HC and CO and high thermal stability, contributes greatly to the low-temperature purification activity of the exhaust gas purification catalyst when the internal combustion engine starts to operate. On the other hand, in the exhaust gas purification catalyst, especially at high temperatures, in order to alleviate the oxygen concentration fluctuations in the exhaust gas and improve the purification performance, it is necessary to fully ensure the OSC (Oxygen Storage Capacity). Based on these viewpoints, various technologies have been developed. For example, Patent Document 1 describes a purification device comprising a catalyst layer including a downstream catalyst layer and an upstream catalyst layer, wherein the upstream catalyst layer and the downstream catalyst layer respectively include a lower layer containing Rh and an upper layer containing Pd, the length of the upstream catalyst layer is greater than 30% and less than 70% of the total length of the substrate, and the Pd loading density of the upstream upper layer is greater than 1 times and less than 3 times that of the downstream upper layer.
[0003] Prior art literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2021-055628 Summary of the invention
[0005] With the introduction of exhaust regulations such as Euro 7 (European Stage 7 Emission Standard, Euro7), the importance of low-temperature purification activity of exhaust gas purification catalysts is increasing. As a method for improving low-temperature purification activity, it is considered to use the catalyst preheating caused by the oxidation reaction of HC and CO of Pd, which contributes greatly to the low-temperature purification activity. For example, as described in Patent Document 1, by configuring a layer containing Pd on the upper side of the catalyst layer and a layer containing Rh on the lower side, the contact frequency between the exhaust gas and the layer containing Pd is increased, thereby improving the preheating of the catalyst and improving the low-temperature purification activity. On the other hand, in this case, the contact frequency between the exhaust gas and the layer containing Rh decreases, so it is likely that the function of the OSC material cannot be fully exerted. Therefore, especially at high temperatures, the OSC may become insufficient.
[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide an exhaust gas purification catalyst capable of improving low-temperature purification activity and sufficiently ensuring OSC.
[0007] In order to solve the above-mentioned problems, the exhaust gas purification catalyst of the present invention is an exhaust gas purification catalyst having a substrate and a catalyst layer arranged on the substrate, characterized in that the catalyst layer has a lower catalyst layer arranged on the substrate and an upper catalyst layer arranged on the lower catalyst layer, the lower catalyst layer includes: a powder material containing a powder carrier and catalyst metal particles supported on the carrier and containing Rh, the upper catalyst layer includes an upstream catalyst layer arranged on the upstream side of the exhaust gas flow direction and a downstream catalyst layer arranged on the downstream side of the exhaust gas flow direction, at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer includes a powder material containing a powder carrier and catalyst metal particles supported on the carrier and containing Pd, and the cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer 50 It is 6 μm or more and 10 μm or less.
[0008] According to the present invention, low-temperature purification activity can be improved and OSC can be sufficiently ensured. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a schematic perspective view of the exhaust gas purification catalyst according to the first embodiment.
[0010] Figure 2 It means Figure 1 The schematic cross-sectional view of a cross section parallel to the extending direction of a unit (cell, cell) of the exhaust gas purifying catalyst shown.
[0011] Figure 3 (a) represents the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer. 50 , a coordinate diagram showing the relationship between Cmax and NOx-T50, Figure 3 (b) is a graph showing the relationship between the weight ratio of the Pd particles in the upstream catalyst layer, Cmax, and NOx-T50.
[0012] Figure 4 (a) is a graph showing the relationship between the coating width of the upstream catalyst layer of the upper catalyst layer, Cmax and NOx-T50, Figure 4 (b) shows the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer. 50A coordinate diagram showing the relationship between the combination of and Cmax and NOx-T50.
[0013] Description of Reference Numerals
[0014] 1: exhaust gas purification catalyst, 10: honeycomb substrate, 12: unit, 14: partition wall, 20: catalyst layer, 30: lower catalyst layer, 40: upper catalyst layer, 40a: upstream catalyst layer, 40b: downstream catalyst layer DETAILED DESCRIPTION
[0015] The following is an explanation of the embodiment of the catalyst for exhaust gas purification of the present invention. Hereinafter, "upstream side" and "downstream side" refer to the upstream side and downstream side of the exhaust gas flow direction, respectively. "Axial direction" refers to the axial direction of the substrate. "Extension direction" refers to the extension direction of the partition wall and the unit, that is, the direction relative to the upstream side and the downstream side, which is roughly the same direction as the axial direction.
[0016] First, a first embodiment is exemplified and an outline of the embodiment is described. Figure 1 It is a schematic perspective view of the exhaust gas purification catalyst according to the first embodiment. Figure 2 It means Figure 1 The schematic cross-sectional view of the cross section parallel to the extending direction of the unit of the exhaust gas purification catalyst shown in FIG. 1 is also a cross-sectional enlarged view of the upstream side catalyst layer of the upper side catalyst layer. Figure 1 and Figure 2 As shown, the exhaust gas purification catalyst 1 of the first embodiment is a so-called direct current type three-way catalyst. The exhaust gas purification catalyst 1 includes a honeycomb substrate 10 (substrate) and a catalyst layer 20 arranged on the honeycomb substrate 10. The honeycomb substrate 10 is a substrate in which a cylindrical frame portion 11 and a partition wall 14 that divides the inner space of the frame portion 11 into a honeycomb shape are integrally formed. The partition wall 14 is a porous body that divides a plurality of units 12 extending from the upstream side end face 10Sa of the honeycomb substrate 10 to the downstream side end face 10Sb. The partition wall 14 includes a plurality of wall portions 14A separated from each other and arranged in parallel, and a plurality of wall portions 14B that are orthogonal to the plurality of wall portions 14A and separated from each other and arranged in parallel, in a manner that the cross section perpendicular to the extension direction of the plurality of units 12 is square. As a result, the cross section perpendicular to the extension direction of the partition wall 14 becomes a grid shape. The plurality of units 12 are adjacent to each other with the partition wall 14 sandwiched therebetween, and their upstream side ends 12a and downstream side ends 12b are open.
[0017] like Figure 2As shown, the catalyst layer 20 has a lower catalyst layer 30 and an upper catalyst layer 40. The lower catalyst layer 30 is arranged on the surface 14s of the unit 12 side of the partition wall 14 in the area from the upstream side end of the partition wall 14 along the extension direction to the downstream side end. The upper catalyst layer 40 is arranged on the surface 30s of the lower catalyst layer 30 in the area from the upstream side end of the partition wall 14 along the extension direction to the downstream side end. The length of the lower catalyst layer 30 in the extension direction (axial direction) relative to the length in the extension direction of the partition wall 14 (the length in the axial direction of the substrate) is 100%. Although not shown, the lower catalyst layer 30 includes a powder material and catalyst metal particles, the powder material includes a powdered carrier composed of carrier particles and a powdered promoter composed of promoter particles, and the catalyst metal particles are supported on the carrier particles and contain Rh (rhodium). Furthermore, the carrier particles of the powdered carrier include carrier particles containing OSC material and carrier particles not containing OSC material. The promoter particles of the powdery promoter do not carry catalytic metal particles, and include promoter particles containing an OSC material and promoter particles not containing an OSC material.
[0018] The upper catalyst layer 40 has: an upstream catalyst layer 40a arranged on the upstream side of the exhaust flow direction, and a downstream catalyst layer 40b arranged on the downstream side of the exhaust flow direction. The upstream catalyst layer 40a extends from the upstream end of the partition wall 14 along the extension direction toward the downstream side to a predetermined position at a distance of 50% of the length of the partition wall 14 in the extension direction, and the downstream catalyst layer 40b extends from the downstream end of the partition wall 14 along the extension direction to the predetermined position. The ratio of the length of the upstream catalyst layer 40a in the extension direction (axial direction) to the length of the partition wall 14 in the extension direction (axial length of the substrate) is 50%. The ratio of the length of the downstream catalyst layer 40b in the extension direction to the length of the partition wall 14 in the extension direction is 50%. As Figure 2 As shown in the enlarged view, the upstream catalyst layer 40a and the downstream catalyst layer 40b include powdered materials and catalyst metal particles 4, the powdered materials include a powdered carrier composed of carrier particles 2 and a powdered promoter composed of promoter particles 6, and the catalyst metal particles 4 are supported on the carrier particles 2 and contain Pd (palladium). Furthermore, the carrier particles 2 of the powdered carrier include carrier particles containing OSC material and carrier particles not containing OSC material. The promoter particles 6 of the powdered promoter include promoter particles containing barium sulfate in addition to promoter particles containing OSC material without supporting the catalyst metal particles 4 and containing OSC material and promoter particles not containing OSC material. The cumulative 50% particle size D in the volume-based particle size distribution of the powdered material contained in the upstream catalyst layer 40a is: 50 The powder material D contained in the downstream catalyst layer 40b is 6.5 μm.50 The weight of the catalytic metal particles contained in the upstream catalyst layer 40a was 6.5 μm. The ratio of the weight of the catalytic metal particles contained in the upper catalyst layer 40 was 75% by weight.
[0019] In the exhaust gas purifying catalyst 1 of the first embodiment, the powder material D contained in the upstream catalyst layer 40a and the downstream catalyst layer 40b of the upper catalyst layer 40 is 50 By increasing the size of the voids in these layers to be larger than 6 μm as in the past, the size of the voids in these layers can be increased to the same extent as when these layers are formed using a slurry to which a pore-forming material made of an organic resin is added. As a result, the exhaust gas can easily pass through the upstream catalyst layer 40a and the downstream catalyst layer 40b to the same extent as when a slurry to which a pore-forming material made of an organic resin is added is used. Thus, by further increasing the contact frequency between the exhaust gas and the upstream catalyst layer 40a and the downstream catalyst layer 40b containing Pd, the preheating effect brought about by the oxidation reaction of HC and CO of Pd becomes greater, and the preheating property of the catalyst 1 can be improved. In addition, by suppressing the decrease in the contact frequency between the exhaust gas and the lower catalyst layer 30 containing Rh, the function of the OSC material can be fully exerted. Therefore, the low-temperature purification activity can be improved, and OSC can be fully ensured, especially at high temperatures. On the other hand, the D of the powder material contained in the upstream catalyst layer 40a and the downstream catalyst layer 40b 50 By making the thickness of the catalyst 1 smaller than 10 μm, these layers can be made thinner. Thus, the increase in pressure loss can be suppressed. Furthermore, when the upstream catalyst layer 40a and the downstream catalyst layer 40b are formed using a slurry to which a pore-forming material made of an organic resin is added, when the substrate is calcined after the slurry is applied, thermal stress is generated due to the heat caused by the combustion of the pore-forming material. In contrast, in the catalyst 1, these layers can be formed without adding a pore-forming material to the slurry, so the generation of thermal stress can be suppressed. Therefore, since the durability problem can be avoided, multiple types of substrates with thin components can be used as the substrate 10, which can improve the preheating property of the catalyst 1.
[0020] In addition, by making the weight ratio of the catalyst metal particles contained in the upstream catalyst layer 40a relative to the weight of the catalyst metal particles contained in the upper catalyst layer 40 to be 50% by weight or more, the density of Pd in the upstream catalyst layer 40a, which is relatively high in temperature, becomes high, and thus the preheating effect of the oxidation reaction of HC and CO by Pd becomes further increased. Therefore, the preheating property of the catalyst 1 can be efficiently improved, and the low-temperature purification activity can be further improved. On the other hand, by making the weight ratio to be 90% by weight or less, the density of Pd in the downstream catalyst layer 40b does not become too low, and thus the function of the OSC material contained in the downstream catalyst layer 40b and the downstream region of the lower catalyst layer 30 can be fully exerted, and OSC can be further fully ensured. Moreover, by making the length of the upstream catalyst layer 40a in the extension direction relative to the length of the partition wall 14 in the extension direction to be 30% or more, the density of Pd in the downstream catalyst layer 40b does not become too low, and thus OSC can be further fully ensured. On the other hand, by making the ratio of the length of the upstream catalyst layer 40a in the extension direction to the length of the partition wall 14 in the extension direction 70% or less, the density of Pd in the upstream catalyst layer 40a having a relatively high temperature becomes high, so that the preheating property of the catalyst 1 can be efficiently improved, and the low-temperature purification activity can be further improved. Next, the structure of the exhaust gas purification catalyst of the embodiment is described in detail.
[0021] 1. Substrate
[0022] The substrate is not particularly limited, and examples thereof include a honeycomb substrate, etc. The material of the substrate is not particularly limited, and for example, cordierite, etc. are preferred.
[0023] 2. Catalyst layer
[0024] The catalyst layer includes a lower catalyst layer disposed on the substrate and an upper catalyst layer disposed on the lower catalyst layer. The catalyst layer is not particularly limited, for example, when the substrate is a honeycomb substrate, the lower catalyst layer is disposed on the surface of the cell side of the partition wall of the honeycomb substrate, and the upper catalyst layer is disposed on the surface of the lower catalyst layer.
[0025] (1) Lower catalyst layer
[0026] The lower catalyst layer includes a powder material including a powdery carrier, and catalyst metal particles supported on the carrier and containing Rh (rhodium).
[0027] As a powder material, there is no particular limitation as long as it contains a powdered carrier, but it may further contain a powdered promoter. Regarding the powdered carrier and the powdered promoter, they are the same as the powdered carrier and the powdered promoter contained in the upstream catalyst layer of the upper catalyst layer described later. In the case where there are more than two kinds of powdered carrier materials, or in the case where there are one kind of powdered carrier material and one kind of powdered promoter material, the powdered material becomes a mixed powder containing powders of more than two materials. The weight of the powdered material of the lower catalyst layer per 1L capacity of the coating part of the lower catalyst layer as the substrate is not particularly limited, for example, preferably within the range of more than 30g / L and less than 250g / L. Furthermore, the capacity of the coating part of various catalyst layers of the substrate refers to the capacity of the axial region (coating part) of the substrate that is the same as the length of various catalyst layers in the axial direction (including the net volume of the region and the apparent volume of the volume of the internal unit). Catalyst metal particles are not particularly limited as long as they contain Rh. Regarding the average particle size of the catalyst metal particles, it is the same as the catalyst metal particles contained in the upstream catalyst layer of the upper catalyst layer described later. The weight of the catalyst metal particles of the lower catalyst layer per 1L volume of the coated portion of the lower catalyst layer of the substrate is not particularly limited, and is preferably within a range of 0.05 g / L or more and 5 g / L or less, for example. The lower catalyst layer is not particularly limited, and is preferably, for example, extending from the downstream side end of the substrate (partition wall) along the axial direction (extension direction) toward the upstream side to a predetermined position at a distance of more than 80% and less than 100% of the length in the axial direction away from the substrate.
[0028] (2) Upper catalyst layer
[0029] The upper catalyst layer includes an upstream catalyst layer disposed on the upstream side of the exhaust gas flow direction and a downstream catalyst layer disposed on the downstream side of the exhaust gas flow direction. At least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer includes: a powder material containing a powder carrier, and catalyst metal particles supported on the carrier and containing Pd (palladium). The cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer is 50 The cumulative 50% particle size D in the volume-based particle size distribution of the powder material is 6 μm or more and 10 μm or less. 50 For example, the particle size distribution can be measured by a laser diffraction particle size distribution measuring device. The upper catalyst layer is not particularly limited, but it is preferred that both the upstream catalyst layer and the downstream catalyst layer contain the powder material and the catalyst metal particles. As the upper catalyst layer, it is preferred that the powder material contained in both the upstream catalyst layer and the downstream catalyst layer has a particle size distribution of 0.1-1.0 wt. % and a particle size distribution of 1.1-1.0 wt. % respectively. 50 All of them are 6 μm or more and 10 μm or less.
[0030] The powder material is not particularly limited as long as it contains a powdery carrier, and may further contain a powdery co-catalyst. The powdery carrier is composed of carrier particles that support catalytic metal particles. The material of the powdered carrier is not particularly limited, and examples thereof include Al2O3 (aluminum oxide), CeO2 (cerium oxide), ZrO2 (zirconia), etc., and their solid solutions (such as CZ composite oxide (cerium oxide-zirconia composite oxide), etc.), and two or more of them may be used. The material of the powdered carrier may not contain an OSC material, but preferably contains an OSC material. The OSC material is not particularly limited, and examples thereof include CeO2, ZrO2, and CZ composite oxides. The powdered promoter is composed of promoter particles that do not carry catalyst metal particles. The material of the powdered promoter is not particularly limited, and in addition to the same material as the material of the powdered carrier, examples thereof include sulfates of alkaline earth metals such as barium sulfate (BaSO4), and two or more of them may be used. In the case where the material of the powdered carrier is two or more, or in the case where the material of the powdered carrier is one and the material of the powdered promoter is one or more, the powdered material becomes a mixed powder containing powders of two or more materials. In addition, D of the powdered material in this case 50 D for mixed powder 50 The weight of the powder material of the upstream catalyst layer per 1L of the coated portion of the upstream catalyst layer of the substrate and the weight of the powder material of the downstream catalyst layer per 1L of the coated portion of the downstream catalyst layer of the substrate are not particularly limited, and are preferably within the range of 30 g / L or more and 250 g / L or less, for example.
[0031] The catalyst metal particles are not particularly limited as long as they contain Pd. The average particle size of the catalyst metal particles is, for example, greater than 0.1 nm and less than 100 nm. Furthermore, the average particle size of the catalyst metal particles refers to the average value of the particle size obtained by, for example, observing the catalyst layer using TEM or the like. As the upper catalyst layer, it is preferred that the weight of the catalyst metal particles contained in the upstream catalyst layer is greater than 50% by weight and less than 90% by weight relative to the weight of the catalyst metal particles contained in the upper catalyst layer. Because this can further improve the low-temperature purification activity and can more fully ensure OSC. Furthermore, the catalyst metal particles contained in the upper catalyst layer refer to the total of the catalyst metal particles contained in the upstream catalyst layer and the catalyst metal particles contained in the downstream catalyst layer. The weight of the catalyst metal particles of the upstream catalyst layer per 1L capacity of the coating portion of the upstream catalyst layer as the substrate, and the weight of the catalyst metal particles of the downstream catalyst layer per 1L capacity of the coating portion of the downstream catalyst layer of the substrate, are not particularly limited, for example, preferably in the range of 0.05 g / L or more and 5 g / L or less.
[0032] As the upper catalyst layer, the ratio of the axial length (extension direction) of the upstream catalyst layer to the axial length of the substrate (the length in the extension direction of the partition wall) is preferably 30% or more and 70% or less. Because this can further improve the low-temperature purification activity and can more fully ensure OSC. As such an upper catalyst layer, the upstream catalyst layer preferably extends from the upstream side end of the substrate (partition wall) along the axial direction (extension direction) to the downstream side to a predetermined position at a distance of more than 30% and less than 70% of the axial length of the substrate, and the downstream catalyst layer preferably extends axially from the downstream side end of the substrate to the predetermined position.
[0033] [Example]
[0034] Hereinafter, the exhaust gas purification catalyst according to the embodiment will be described in more detail with reference to Examples and Comparative Examples.
[0035] 1. Raw materials for the substrate and catalyst layer of exhaust gas purification catalysts
[0036] (1) Base material:
[0037] 875cc (600 hexagonal cells with 2 mil wall thickness) cordierite honeycomb substrate
[0038] (2) Raw materials of catalyst layer:
[0039] a. Material 1 (Al2O3):
[0040] Powder containing La2O3 composite Al2O3 (La2O3: 1 wt% to 10 wt%) particles
[0041] b. Material 2 (ACZ):
[0042] Powder containing Al2O3-CeO2-ZrO2 composite oxide (CeO2: 15 wt% to 30 wt%) particles (Nd2O3, La2O3, Y2O3 are added in trace amounts to achieve high heat resistance)
[0043] c. Material 3 (AZ):
[0044] Powder containing Al2O3-ZrO2 composite oxide (ZrO2: 50 wt% to 80 wt%) particles (Nd2O3, La2O3, Y2O3 are added in trace amounts to achieve high heat resistance)
[0045] d. Material 4 (pyrochlore-type CZ composite oxide):
[0046] Contains 45 wt% to 55 wt% CeO2, 40 wt% to 50 wt% ZrO2, 1 wt% to 5 wt% Pr6O11 Composite oxide particle powder
[0047] e. Material 5 (barium sulfate):
[0048] Powder containing barium sulfate particles
[0049] f. Material 6 (palladium nitrate):
[0050] Powder containing palladium nitrate particles
[0051] g. Material 7 (rhodium nitrate):
[0052] Powder containing rhodium nitrate particles
[0053] h. Material 8 (AZ loaded with Rh):
[0054] Powder containing AZ particles carrying Rh particles
[0055] i. Material 9 (Al2O3 loaded with Pd):
[0056] Powder containing Al2O3 particles carrying Pd particles
[0057] j. Material 10 (ACZ loaded with Pd):
[0058] Powder containing ACZ particles carrying Pd particles
[0059] 2. Preparation of catalyst for exhaust purification
[0060] [Comparative Example 1]
[0061] (Formation of Catalyst Layer Below Catalyst Layer)
[0062] First, material 7 and material 3 are added to distilled water under stirring, and then dried and calcined to prepare material 8. Next, material 8, material 1, material 2, material 4, and Al2O3-based binder are added to distilled water under stirring to prepare suspended slurry 1. At this time, the cumulative 50% particle size D in the volume-based particle size distribution of the mixed powder obtained by mixing material 3 (powdered carrier), material 1 (powdered co-catalyst), material 2 (powdered co-catalyst), and material 4 (powdered co-catalyst) in the slurry 1 is 0.1747 W / cm2. 50 (The cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in the lower catalyst layer 50 ) is adjusted to 5.0μm.
[0063] Next, the slurry 1 is made to flow into the unit of the substrate from the downstream side end, and the unnecessary part is blown away with a blower, thereby coating the material of the lower catalyst layer on the surface of the unit side of the substrate's partition wall to prepare the precursor layer of the lower catalyst layer. At this time, in each 1L volume of the coating portion of the lower catalyst layer of the substrate, the Rh-converted weight of material 7 is 0.25g / L-zone, the weight of material 1 is 30g / L-zone, the weight of material 2 is 60g / L-zone, the weight of material 3 is 30g / L-zone, and the weight of material 4 is 5g / L-zone. In addition, the ratio of the length in the extension direction (axial direction) of the precursor layer of the lower catalyst layer to the length in the extension direction of the partition wall (the length in the axial direction of the substrate) (hereinafter sometimes referred to as "the coating width of the lower catalyst layer") is 100%. Finally, after the water is volatilized for 2 hours in a dryer maintained at 120°C, it is calcined at 500°C for 2 hours in an electric furnace, thereby forming a lower catalyst layer on the surface of the unit side of the partition wall of the substrate.
[0064] (Formation of upstream catalyst layer of upper catalyst layer)
[0065] Next, material 6, material 1, material 2, material 5, and an Al2O3-based binder were added to distilled water under stirring to prepare a suspended slurry 2. At this time, material 9 was prepared from material 6 and material 1, and material 10 was prepared from material 6 and material 2. Furthermore, the cumulative 50% particle size D in the volume-based particle size distribution of the mixed powder obtained by mixing material 1 (powdered carrier), material 2 (powdered carrier), and material 5 (powdered co-catalyst) in slurry 2 was 1.34 mm / s. 50 (The cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in the upstream catalyst layer 50 ) is adjusted to 5.0μm.
[0066] Next, the slurry 2 is made to flow into the unit of the substrate from the upstream side end, and the unnecessary part is blown away with a blower, thereby coating the material of the upstream catalyst layer of the upper catalyst layer on the surface of the lower catalyst layer to prepare the precursor layer of the upstream catalyst layer. At this time, in each 1L capacity of the coating portion of the upstream catalyst layer of the substrate, the weight of the Pd conversion of material 6 is 2.25g / L-zone, the weight of material 1 is 25g / L-zone, the weight of material 2 is 75g / L-zone, and the weight of material 5 is 15g / L-zone. In addition, the ratio of the length in the extension direction of the precursor layer of the upstream catalyst layer to the length in the extension direction of the next wall (hereinafter sometimes referred to as "the coating width of the upstream catalyst layer") is 50%. Finally, the water is evaporated and calcined in the same manner as when the lower catalyst layer is formed, thereby forming the upstream catalyst layer on the surface of the lower catalyst layer.
[0067] (Formation of the Downstream Side Catalyst Layer of the Upper Side Catalyst Layer)
[0068] Next, material 6, material 1, material 2, material 5, and an Al2O3-based binder were added to distilled water under stirring to prepare a suspended slurry 3. At this time, material 9 was prepared from material 6 and material 1, and material 10 was prepared from material 6 and material 2. Furthermore, the cumulative 50% particle size D in the volume-based particle size distribution of the mixed powder obtained by mixing material 1 (powdered carrier), material 2 (powdered carrier), and material 5 (powdered co-catalyst) in the slurry 3 was 1.33 mm / s. 50 (The cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in the downstream catalyst layer 50 ) is adjusted to 5.0μm.
[0069] Next, the slurry 3 is made to flow into the unit of the substrate from the downstream side end, and the unnecessary part is blown away with a blower, thereby coating the material of the downstream catalyst layer of the upper catalyst layer on the surface of the lower catalyst layer to prepare the precursor layer of the downstream catalyst layer. At this time, in each 1L capacity of the coating part of the downstream catalyst layer of the substrate, the weight of material 6 converted to Pd is 0.75g / L-zone, the weight of material 1 is 25g / L-zone, the weight of material 2 is 75g / L-zone, and the weight of material 5 is 15g / L-zone. In addition, the ratio of the length in the extension direction of the precursor layer of the downstream catalyst layer to the length in the extension direction of the next wall (hereinafter sometimes referred to as "the coating width of the downstream catalyst layer") is 50%. Finally, the water is evaporated and calcined in the same way as when the lower catalyst layer is formed, thereby forming the downstream catalyst layer on the surface of the lower catalyst layer. Thus, a catalyst for exhaust purification is produced.
[0070] [Example 1]
[0071] When preparing the slurry 2 in forming the upstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50 When preparing slurry 3 in forming the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 6.5 μm. 50 The particle size was adjusted to 6.5 μm. Except for this, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1. The exhaust gas purifying catalyst of Example 1 is an example of the exhaust gas purifying catalyst of the first embodiment.
[0072] [Example 2]
[0073] When preparing the slurry 2 in forming the upstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50When preparing slurry 3 in forming the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 8.0 μm. 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0074] [Example 3]
[0075] When preparing the slurry 2 in forming the upstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50 When preparing slurry 3 in forming the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 10.0 μm. 50 The particle size was adjusted to 10.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0076] [Comparative Example 2]
[0077] When preparing the slurry 2 in forming the upstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50 When preparing slurry 3 in forming the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 12.0 μm. 50 The particle size was adjusted to 12.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0078] [Example 4]
[0079] In forming the upstream catalyst layer of the upper catalyst layer, the amount of material 6 added was reduced when preparing the slurry 2, so that the Pd-converted weight of the material 6 per 1L volume of the coating portion of the upstream catalyst layer of the substrate became 0.75 g / L-zone, and the D of the mixed powder was reduced. 50 In addition, in the formation of the downstream catalyst layer of the upper catalyst layer, the amount of material 6 added when preparing the slurry 3 was increased, so that the Pd-converted weight of the material 6 per 1L volume of the coating portion of the downstream catalyst layer of the substrate became 2.25 g / L-zone, and the D of the mixed powder was adjusted to 8.0 μm. 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0080] [Example 5]
[0081] In forming the upstream catalyst layer of the upper catalyst layer, the amount of material 6 added when preparing the slurry 2 was increased so that the Pd-converted weight of material 6 per 1L volume of the coating portion of the upstream catalyst layer of the substrate became 2.70 g / L-zone, and the D of the mixed powder was changed to50 In addition, in the formation of the downstream catalyst layer of the upper catalyst layer, the amount of material 6 added was reduced when preparing the slurry 3, so that the Pd-converted weight of the material 6 per 1L volume of the coating portion of the downstream catalyst layer of the substrate became 0.30 g / L-zone, and the D of the mixed powder was adjusted to 8.0 μm. 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0082] [Example 6]
[0083] In forming the upstream catalyst layer of the upper catalyst layer, the amount of material 6 added during the preparation of the slurry 2 was increased so that the Pd-converted weight of material 6 per 1L volume of the coating portion of the upstream catalyst layer of the substrate became 3.00 g / L-zone, and the D of the mixed powder was changed to 50 In the formation of the downstream catalyst layer of the upper catalyst layer, the material 6 was not added when preparing the slurry 3, so that the Pd-converted weight of the material 6 per 1L volume of the coating portion of the downstream catalyst layer of the substrate became 0.00 g / L-zone, and the D of the mixed powder was adjusted to 8.0 μm. 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0084] [Example 7]
[0085] In forming the upstream catalyst layer of the upper catalyst layer, when preparing the slurry 2, the D of the mixed powder is 50 The coating width of the upstream catalyst layer was adjusted to 8.0 μm, thereby making the coating width of the upstream catalyst layer 20%. In addition, in the formation of the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 8.0 μm when preparing the slurry 3. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was adjusted to 80%. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0086] [Example 8]
[0087] In forming the upstream catalyst layer of the upper catalyst layer, when preparing the slurry 2, the D of the mixed powder is 50 The coating width of the upstream catalyst layer was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was changed to 35%. In the formation of the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 8.0 μm when preparing the slurry 3. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was adjusted to 65%. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0088] [Example 9]
[0089] In forming the upstream catalyst layer of the upper catalyst layer, when preparing the slurry 2, the D of the mixed powder is 50 The coating width of the upstream catalyst layer was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was 65%. In addition, in the formation of the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 8.0 μm when preparing the slurry 3. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was adjusted to 35%. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0090] [Example 10]
[0091] In forming the upstream catalyst layer of the upper catalyst layer, when preparing the slurry 2, the D of the mixed powder is 50 The coating width of the upstream catalyst layer was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was 80%. In addition, in the formation of the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder was adjusted to 8.0 μm when preparing the slurry 3. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was changed to 20%. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0092] [Example 11]
[0093] When preparing the slurry 2 in forming the upstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0094] [Comparative Example 3]
[0095] When preparing the slurry 3 in forming the downstream catalyst layer of the upper catalyst layer, the D of the mixed powder is 50 The particle size was adjusted to 8.0 μm. Except for this, an exhaust gas purification catalyst was prepared in the same manner as in Comparative Example 1.
[0096] 3. Durability test
[0097] For each exhaust purification catalyst of the comparative example and the embodiment, a durability test was conducted using an actual engine. Specifically, each exhaust purification catalyst was installed in the exhaust system of a V-type 8-cylinder engine, and the exhaust gas of the stoichiometric ratio and the lean atmosphere was repeatedly flowed for a certain period of time (ratio of 3:1) at a catalyst bed temperature of 900°C for 50 hours to conduct the durability test.
[0098] 4. Performance Evaluation
[0099] For each exhaust purification catalyst of the comparative example and the embodiment that were subjected to the durability test, the performance evaluation was carried out using an actual engine. Specifically, each exhaust purification catalyst was installed in the exhaust system of an L-type 4-cylinder engine, and the OSC (oxygen storage capacity), low-temperature purification activity and pressure loss were evaluated as follows, and the relationship between the composition of the exhaust purification catalyst of the comparative example and the embodiment and their performance was investigated.
[0100] [OSC]
[0101] For each exhaust gas purification catalyst, the intake air temperature was 600°C and the A / F of the intake atmosphere was varied between 14.1 and 15.1 in a short period with an amplitude. In this case, the excess or deficiency of oxygen was calculated based on the difference between the theoretical ratio point and the output of the A / F sensor by the formula: OSC[g] = 0.23 × ΔA / F × the amount of injected fuel, and Cmax (maximum oxygen absorption) [g) was obtained. The results are shown in the following Table 1.
[0102] [Low temperature purification activity]
[0103] For each exhaust gas purification catalyst, exhaust gas with an intake atmosphere A / F of 14.4 was flowed at Ga = 30 g / s, and the intake air temperature was slowly increased from 200°C to 500°C. In this case, the NOx concentrations of the intake and exhaust gases were measured at each intake air temperature, and the NOx purification rate was calculated. The intake air temperature at the time when 50% of NOx was purified was taken as the NOx purification rate. X -T50 (NOx 50% purification temperature) [°C] was measured. The results are shown in Table 1 below.
[0104] [Pressure loss]
[0105] For each exhaust gas purifying catalyst, the pressure loss when air was allowed to flow through the exhaust gas purifying catalyst was measured.
[0106] Table 1
[0107]
[0108] [Relationship between catalyst composition and performance]
[0109] Based on the above performance evaluation results, regarding the exhaust gas purification catalysts of Examples 1 to 3 and Comparative Examples 1 and 2, the D of the mixed powder of the upstream catalyst layer (slurry 2) and the downstream catalyst layer (slurry 3) of the upper catalyst layer was investigated. 50 , and the relationship between Cmax and NOx-T50. The results are shown in Figure 3 (a) In addition, regarding the exhaust gas purification catalysts of Examples 1 to 3 and Comparative Examples 1 and 2, the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer was investigated.50 Relationship with pressure loss. Figure 3 As shown in (a), the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer increases. 50 As the Cmax increases, the NOx-T50 tends to decrease. 50 When the diameter is 6 μm or more, both the effects of increasing Cmax and reducing NOX-T50 can be fully obtained. 50 The results of the investigation on the relationship between D 50 When the particle size is 10 μm or less, the pressure loss can be suppressed to such an extent that the commercial quality of the exhaust gas purification catalyst can be ensured.
[0110] In addition, regarding the exhaust gas purification catalysts of Example 2 and Examples 4 to 6, the relationship between the ratio of the weight of the Pd particles contained in the upstream catalyst layer to the weight of the Pd particles contained in the upper catalyst layer and Cmax and NOx-T50 was investigated. The results are shown in Figure 3 (b) If Figure 3 As shown in (b), as the weight proportion of the Pd particles in the upstream catalyst layer increases, there is a tendency for NOx-T50 to decrease, and Cmax is greater when the weight proportion of the Pd particles in the upstream catalyst layer is 90 weight % or less than when it is greater than 90 weight %. It is believed that when the weight proportion of the Pd particles in the upstream catalyst layer is greater than 50 weight % and less than 90 weight %, both effects of increasing Cmax and reducing NOx-T50 can be obtained at a high level. In addition, for the exhaust purification catalysts of Example 2 and Examples 7 to 10, the coating width of the upstream catalyst layer of the upper catalyst layer and its relationship with Cmax and NOx-T50 were investigated. The results are shown in Figure 4 (a). Figure 4 As shown in (a), there is a tendency that Cmax increases as the coating width of the upstream catalyst layer increases, and NOx-T50 decreases as the coating width of the upstream catalyst layer decreases. It is believed that when the coating width of the upstream catalyst layer is 30% or more and 70% or less, both effects of increasing Cmax and reducing NOx-T50 can be obtained at a high level. In addition, regarding the exhaust gas purification catalysts of Examples 2 and 11 and Comparative Example 3, the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer was investigated. 50 The combination of and the relationship between Cmax and NOx-T50. The results are shown in Figure 4 (b) If Figure 4 As shown in (b), D of both the upstream catalyst layer and the downstream catalyst layer 50 In Example 2, the D of the upstream catalyst layer is 8 μm. 50The D of the downstream catalyst layer is 8 μm. 50 Compared with Example 11 in which the D of the downstream catalyst layer is 5 μm, Cmax is larger and NOx-T50 is lower. 50 The D of the upstream catalyst layer is 8 μm and 50 Compared with Comparative Example 3, which has a D of 5 μm, Cmax is larger and NOx-T50 is lower. It is believed that the D of the upstream catalyst layer is larger than that of the downstream catalyst layer. 50 When it becomes larger, it contributes more to improving Cmax and reducing NOx-T50.
[0111] As mentioned above, although embodiment of the present invention is described in detail, the present invention is not limited to the above-mentioned embodiment, and various design changes can be made within the scope of the spirit of the present invention described in the claims.
Claims
1. An exhaust gas purification catalyst comprising a substrate and a catalyst layer provided on the substrate, characterized in that: The catalyst layer includes: a lower catalyst layer provided on the substrate, and an upper catalyst layer provided on the lower catalyst layer. The lower catalyst layer includes: a powder material including a powdered carrier, and catalyst metal particles supported on the carrier and containing rhodium. The upper catalyst layer includes an upstream catalyst layer disposed on the upstream side in the exhaust gas flow direction, and a downstream catalyst layer disposed on the downstream side in the exhaust gas flow direction. At least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer comprises: a powder material including a powdered carrier, and catalyst metal particles containing palladium supported on the carrier, The cumulative 50% particle size D in the volume-based particle size distribution of the powder material contained in at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer is 50 It is 6 μm or more and 10 μm or less.
2. The exhaust gas purification catalyst according to claim 1, characterized in that: A ratio of the weight of the catalytic metal particles contained in the upstream catalyst layer to the weight of the catalytic metal particles contained in the upper catalyst layer is 50% by weight or more and 90% by weight or less.
3. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: A ratio of a length of the upstream catalyst layer in the axial direction to a length of the substrate in the axial direction is 30% or more and 70% or less.
Citation Information
Patent Citations
Exhaust gas purification apparatus
JP2021055628A